2013
DOI: 10.1016/j.psyneuen.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Chronicity of depressive problems and the cortisol response to psychosocial stress in adolescents: The TRAILS study

Abstract: Clinical and epidemiological studies, further supported by meta-analytic studies, indicate a possible association between chronicity (i.e., persistence or recurrence) of depression and hypothalamic-pituitary-adrenal (HPA) axis responsiveness to psychosocial stress. In the present study, we examined whether and how chronicity of depressive problems predicts cortisol responses to a standardized social stress test in adolescents. Data were collected in a high-risk focus sample (n=351) of the Tracking Adolescents'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 43 publications
6
78
0
4
Order By: Relevance
“…Badanes and colleagues (2011) reported that low cortisol output across the day was associated with higher scores on a measure of emotional distress in a sample of preschoolers, and Sontag-Padilla et al (2012) observed that self-reported distress symptoms were negatively associated with cortisol reactivity to a pain stressor among girls who had evidence of early adrenarche. Furthermore, our results on the association between low cortisol output and exposure to depression over time are consistent with a recently published study of adolescents, for whom depression scores were obtained at ages 11, 13, and 16 years of age (Booij et a l., 2013). In that study, high cortisol output in response to a social stressor at age 16 was associated with past year depression, whereas adolescents who had experienced chronic depression symptoms from 11 to 16 year of age had lower and flatter cortisol output during and after exposure to the social stressor.…”
Section: Discussionsupporting
confidence: 92%
“…Badanes and colleagues (2011) reported that low cortisol output across the day was associated with higher scores on a measure of emotional distress in a sample of preschoolers, and Sontag-Padilla et al (2012) observed that self-reported distress symptoms were negatively associated with cortisol reactivity to a pain stressor among girls who had evidence of early adrenarche. Furthermore, our results on the association between low cortisol output and exposure to depression over time are consistent with a recently published study of adolescents, for whom depression scores were obtained at ages 11, 13, and 16 years of age (Booij et a l., 2013). In that study, high cortisol output in response to a social stressor at age 16 was associated with past year depression, whereas adolescents who had experienced chronic depression symptoms from 11 to 16 year of age had lower and flatter cortisol output during and after exposure to the social stressor.…”
Section: Discussionsupporting
confidence: 92%
“…Greater cortisol responses have been reported for depressed compared to non-depressed adolescents (Rao et al, 2008), dysphoric post-pubertal youth compared to non-dysphoric youth (Hankin et al, 2010), and adolescents with more recent onset of depressive symptoms (Booij et al, 2013). In contrast, blunted cortisol responses have been reported for dysphoric pre-pubertal youth compared to non-dysphoric youth (Hankin et al, 2010), adolescents with more severe depression severity (Harkness et al, 2011), adolescents with internalizing symptoms (Spies et al, 2011), children with higher self-reported depressive symptoms (Dieleman et al, 2010), children with current, past or sub-syndromal MDD (Suzuki et al, 2013), and adolescents with more chronic depressive symptoms (Booij et al, 2013). Taken together, these findings suggest that alterations in cortisol reactivity are not limited to youth with depressive diagnoses and may be determined by a variety of factors including depression severity and developmental timing.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining HPA-axis responses to psychosocial stressors have been equivocal. Some have linked greater post-stress cortisol with depression symptoms (Booij et al, 2013) and diagnosis (Rao et al, 2008). Yet, whether such findings reflect excitatory (more intense/prolonged activation) or inhibitory factors (e.g.…”
Section: Introductionmentioning
confidence: 99%